Mrs. Claus and the Santaland slayings - Ireland, Liz (Kensington Books, 2020)
"Love is full of surprises - though few compare to realizing that you're marrying the real-life Santa. April Claus dearly loves her new husband, Nick, but adjusting to life in the North Pole is not all sugarplums and candy canes. Especially when a cantankerous elf named Giblet Hollyberry is killed - felled by a black widow spider in his stocking - shortly after publicly arguing with Nick. Christmastown is hardly a hotbed of crime, aside from mishaps caused by too much eggnog, but April disagrees with Constable Crinkle's verdict of accidental death. As April sets out to find the culprit, it'll mean putting the future of Christmas on the line - and hoping her own name isn't on a lethal naughty list . . ."--Publisher.